Charwaha Schools in Bihar - A Preliminary Observation 1992-93 - Planning Commission (Planning Commission, 1992)
The Charwaha Schools Evaluation Report by the Programme Evaluation Organisation (PEO) assesses the implementation of the Charwaha Schools Scheme in Bihar, launched in 1991 to provide integrated development services to rural poor, focusing on education, vocational training, and community development. Out of 61 initiated schools, only 34 are functional, with infrastructure remaining underdeveloped and formal education limited to a few locations. Non-formal education and some vocational training are operational, with 1,445 beneficiaries enrolled, 33% of whom are female and 46% from scheduled castes. Key challenges include inadequate facilities, resource shortages, and poor inter-departmental coordination. Recommendations highlight enhancing coordination among stakeholders, investing in infrastructure, diversifying vocational programs, and establishing regular monitoring and feedback mechanisms to improve program effectiveness and community impact.
Programme Evaluation Organisation Planning Commission (Government of India) New Delhi 1992
Programme Evaluation Organisation Planning Commission (Government of India)
Keywords: Charwaha Schools; Rural Education; Vocational Training; Community Development; Infrastructure; Enrollment; Non-Formal Education; Female Participation; Scheduled Castes; Integrated Services; Programme Evaluation; Bihar